2021
DOI: 10.1177/20563051211063470
|View full text |Cite
|
Sign up to set email alerts
|

Social Media and Political Dissent in Russia and Belarus: An Introduction to the Special Issue

Abstract: The special issue focuses on the roles of socially mediated communication in expressing, aggregating, and shaping political dissent and discontent in Russia and Belarus at the borderline between the 2010s and 2020s. Lately, these post-Soviet countries have demonstrated the growth of restrictive trends in both politics and the public sphere reciprocated by increasing street protest and online polarization. The six papers of the special issue come from the Seventh Annual Conference “Comparative Media Studies in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 27 publications
0
12
0
1
Order By: Relevance
“…However, despite Twitter being extremely multi-lingual both within and beyond such discussions, there are no studies that apply abstractive summarization to tweets on multiple languages. Second, tweets are too short to summarize, but their accumulation into author, thread, or sub-topic pools, in line with the concept of cumulative deliberation [61], is what matters within heated discussions for public opinion formation. However, it has not been tested how the neural-network summarization models would work on the pools of tweets.…”
Section: Post Title Post Summary Comment Summarymentioning
confidence: 99%
“…However, despite Twitter being extremely multi-lingual both within and beyond such discussions, there are no studies that apply abstractive summarization to tweets on multiple languages. Second, tweets are too short to summarize, but their accumulation into author, thread, or sub-topic pools, in line with the concept of cumulative deliberation [61], is what matters within heated discussions for public opinion formation. However, it has not been tested how the neural-network summarization models would work on the pools of tweets.…”
Section: Post Title Post Summary Comment Summarymentioning
confidence: 99%
“…Resistance is an inseparable component of information and misinformation campaigns, and it uses a wide repertoire that ranges from actions on the ground to digital activism and social media campaigns. Social media in non-democratic societies, including Russia, have been shown to support resistance through political opposition and challenges to the dominant state-affiliated discourses (Bodrunova, 2021). An analysis of the role of social media in the Arab Spring, for example, has demonstrated that online conversations preceded major events on the ground and that having an active online public sphere contributed to a wider dissemination of democratic values (Howard et al, 2011).…”
Section: Background: (Mis)information Digital Activism and Resistancementioning
confidence: 99%
“…The formulation of a master narrative requires access to information resources (Garrett 2006;S. A. Greene 2022;Jost et al 2018;Onuch, Mateo, and Waller 2020;Tufekci and Wilson 2012) and thus, it is expected that protesters will distinguish themselves from non-protesters in their media consumption patterns (Aday et al 2013;Bodrunova 2021;Couldry, Livingstone, and Markham 2016;S. A. Greene 2022;Kazharski and Kubová 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The formulation of a master narrative requires access to information resources (Garrett 2006; S. A. Greene 2022; Jost et al 2018; Onuch, Mateo, and Waller 2020; Tufekci and Wilson 2012) – and thus, it is expected that protesters will distinguish themselves from non-protesters in their media consumption patterns (Aday et al 2013; Bodrunova 2021; Couldry, Livingstone, and Markham 2016; S. A. Greene 2022; Kazharski and Kubová 2021). In Belarus, observers have made reference to the protesters’ use of particular social media platforms like Telegram and non-state media channels like Nexta and Belsat (S. A. Greene 2022; Herasimenka et al 2020; Wijermars and Lokot 2022).…”
Section: Introductionmentioning
confidence: 99%